2020
DOI: 10.1002/mds.27996
|View full text |Cite
|
Sign up to set email alerts
|

Debugging Adaptive Deep Brain Stimulation for Parkinson's Disease

Abstract: A BS TRACT: Deep brain stimulation (DBS) is a successful treatment for patients with Parkinson's disease. In adaptive DBS, stimulation is titrated according to feedback about clinical state and underlying pathophysiology. This contrasts with conventional stimulation, which is fixed and continuous. In acute trials, adaptive stimulation matches the efficacy of conventional stimulation while delivering about half the electrical energy. The latter means potentially fewer side-effects. The next step is to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 63 publications
0
71
1
Order By: Relevance
“…Several clinical trials [ 9 11 , 18 , 32 , 52 54 ], including the present study, have demonstrated that beta oscillations in the STN correlate with bradykinesia and rigidity in PD patients [ 59 ]. For that reason, beta oscillations are likely to play a central role in future aDBS trials [ 60 , 61 ]. With the advent of new stimulation devices that are able to perform chronic LFP-recordings, the next step towards implementing beta-based aDBS in the clinical practice will be to explore the clinical benefits and limitations of aDBS in real-life situations.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials [ 9 11 , 18 , 32 , 52 54 ], including the present study, have demonstrated that beta oscillations in the STN correlate with bradykinesia and rigidity in PD patients [ 59 ]. For that reason, beta oscillations are likely to play a central role in future aDBS trials [ 60 , 61 ]. With the advent of new stimulation devices that are able to perform chronic LFP-recordings, the next step towards implementing beta-based aDBS in the clinical practice will be to explore the clinical benefits and limitations of aDBS in real-life situations.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the mechanisms of action of DBS could enable development of DBS strategies that are more specific, causing fewer side-effects, and even more effective, should it prove possible to directly counter the key malfunctions in neural circuits. In particular, there has been much recent interest in the possibility of controlling DBS using feedback from electrophysiological signals ( Bouthour et al, 2019 ; Little and Brown, 2020 ; Lozano et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, reduced activities in the beta band and increases in power in the tremor frequency band, corresponding to the theta band (3–7 Hz), in the STN, as well as reduced basal ganglia-cortical coherence in the beta frequency band have been observed during the presence of resting tremor in Parkinson’s disease ( Hirschmann et al, 2013 ; Qasim et al, 2016 ; Asch et al, 2020 ). Moreover, one in five patients shows resurgence of tremor if DBS is only switched on when STN beta activity is high ( Little and Brown, 2020 ). These observations raise the possibility that neurofeedback training that suppresses beta oscillations in the STN may not improve, even worsen, resting tremor in Parkinsonian patients.…”
Section: Introductionmentioning
confidence: 99%